2006
DOI: 10.1108/17410400610641735
|View full text |Cite
|
Sign up to set email alerts
|

In search of the common wealth: a service‐profit chain for the public sector

Abstract: PurposeTo provide public sector organizations with a development map to achieve employee and customer satisfaction and to align organizational processes for goal achievement.Design/methodology/approachThe paper re‐works the highly influential and widely validated service‐profit chain and presents an analogous model, which reflects the essential differences of public sector organizations.FindingsIt was found that there is a direct link between the achievement of the organizational goal and the organization's et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…Currall et al, (2005) found pay satisfaction to be positively related to performance and negatively related to employee turnover intentions. Similarly, the results of another study by Davis (2006) also showed general job satisfaction to be strongly and negatively related to turnover intentions (r = -.69). Job satisfaction has been shown to be the main predictor of turnover intention (Larrabee, et al, 2003;Parry, 2008).…”
Section: Continuance Commitmentmentioning
confidence: 54%
“…Currall et al, (2005) found pay satisfaction to be positively related to performance and negatively related to employee turnover intentions. Similarly, the results of another study by Davis (2006) also showed general job satisfaction to be strongly and negatively related to turnover intentions (r = -.69). Job satisfaction has been shown to be the main predictor of turnover intention (Larrabee, et al, 2003;Parry, 2008).…”
Section: Continuance Commitmentmentioning
confidence: 54%
“…However, there has been some exploration in a public sector context (see for example (Price and Brodie 2001;Micheli and Kennerley 2005;Davis 2006). Although there is no common and accepted set of activities to achieve customer focus and good (or appropriate) levels of service, there are several key elements that are prevalent in the literature including; knowing who the customers are, their expectations, requirements and value opportunities (Vandermerwe 2004); developing, articulating and sharing a (compelling) service concept (Clark et al 2000;Goldstein et al 2002); designing and 'engineering' both the service and the experience to deliver the concept (Verma et al 2002;Zomerdijk and Voss 2010); creating a service culture and customer-focused mindset (Skalen and Strandvik 2005;Johnston 2008) and; measuring and assessing the service from the customer's point of view (Olsen and Johnson 2003).…”
Section: Customer Focusmentioning
confidence: 99%
“…Cinca et al, 2003;Davis, 2006;Euske, 2003). It is also shown that other intangible resources such as the establishment of external and internal relationships, the maintenance of documents and the existence of factors such as trust and motivation play an important role in the efficient management of knowledge (Cong and Pandya, 2003).…”
Section: Impact Of Contextual Factors On Knowledge Management Activitiesmentioning
confidence: 96%